A filling type high thermal conductivity composite press-in material and preparation method thereof
By using a multivariate mixed filling system of epoxy resin and multivariate high thermal conductivity filler in the blast furnace pressing material, a 3D thermal conductivity network path is formed, which solves the problems of poor thermal conductivity and insufficient resistance of the existing pressing material, and significantly improves the thermal conductivity and service life of the blast furnace lining material.
Patent Information
- Application Number
- CN202310104771.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-13
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2043-02-13
AI Technical Summary
The existing pressed sealing materials for blast furnaces have poor thermal conductivity, high temperature resistance, corrosion resistance and adhesion. It is difficult to take into account both thermal conductivity and comprehensive mechanical properties, and cannot meet the long-life needs of blast furnace lining refractory materials.
Using epoxy resin as the thermal conductivity medium material to build a multivariate hybrid filling system, select fillers with high thermal conductivity such as silicon carbide, diamond, carbon nanotubes, boron nitride, copper powder and zirconium copper alloy powder, and mix them through ball mills and mixers to form a 3D thermal conductivity network path with continuous chain or mesh structure to improve the thermal conductivity and mechanical properties of the composite material.
It significantly improves the thermal conductivity, adhesion, high temperature and corrosion resistance of the high-thermal composite pressed material, enhances adhesion, and extends the service life of the blast furnace lining refractory material.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of refractory materials, and in particular to a filling type high thermal conductivity composite press-in material and a preparation method thereof. Background Art
[0002] At present, the design life of a generation of large-scale blast furnaces in my country has reached 15 to 20 years, or even more than 20 years. In order to achieve the longevity of blast furnaces, modern large-scale blast furnaces use refractory materials of different materials according to the cooling system and different parts of the furnace body. The life of the refractory lining of the blast furnace is an important aspect of the longevity of the entire blast furnace. From the perspective of thermodynamics, combined with the actual operating status of the blast furnace, by configuring an effective cooling system and matching it with lining materials with high thermal conductivity and good thermal shock resistance, the hot surface temperature of the refractory material can be reduced, and the high-intensity thermal shock can be resisted to extend the service life of the lining refractory material.
[0003] During smelting, the lining of the blast furnace is constantly eroded by various factors, including thermal shock caused by temperature changes, wear and oxidation caused by furnace charge and high-temperature airflow, erosion by molten iron, alkali metals, etc.; under the damage of various factors, the refractory materials of the lining become thinner, cracked, and fall off, causing damage to the cooling system, and even the furnace shell is directly deformed by heat, forming hot spots or hot areas in the blast furnace. In some blast furnaces that have been in operation for a long time, local redness and deformation are common, resulting in thickness defects in the lining, hot spots and cracks on the surface of the furnace shell, and local overtemperature in the furnace cylinder, which leads to the deterioration of the operating environment in front of the furnace, directly affecting the normal production and service life of the blast furnace, that is, the furnace needs to be shut down for maintenance, which is difficult to shut down and has a long impact time. The lining maintenance should be repaired in a hot state, and the press-in material can improve or solve this kind of problem. The use of high thermal conductivity carbon composite press-in material is used to grout the overheated parts of the blast furnace hearth and furnace bottom area. Press-in repair from outside the furnace is the main way of hot repair. The press-in material requires grouting and pouring to be dense, with sufficient thermal strength, and the grouting should not cause damage to the corresponding treated parts and surrounding refractory materials and equipment. At present, the thermal conductivity of the press-in sealing material for blast furnaces is poor. It has poor high temperature resistance, corrosion resistance and adhesion, and cannot take into account both thermal conductivity and comprehensive mechanical properties at the same time, making it difficult to meet the use requirements. Summary of the invention
[0004] In view of the above problems, the present invention provides a filled high thermal conductivity composite press-in material and a preparation method thereof, constructs a multi-component mixed filling system with epoxy resin as a thermal conductive medium material, and by selecting fillers with high thermal conductivity and improving heat exchange efficiency, the filler particles are in contact with each other, the interface thermal resistance is reduced, and a 3D thermal conductive network path with a continuous chain or mesh structure is formed in the polymer matrix to improve the thermal conductivity of the epoxy resin-based composite material. The press-in material has strong bonding properties, good thermal conductivity, high temperature resistance, corrosion resistance and strong adhesion, thereby improving the service life of the blast furnace.
[0005] The technical solution adopted by the present invention to achieve the above-mentioned purpose is: a filled high thermal conductivity composite press-in material, which is made of the following raw materials in parts by weight: 35-55 parts of silicon carbide, 10-15 parts of diamond, 3-10 parts of carbon nanotubes, 5-10 parts of boron nitride, 2-8 parts of copper powder, 2-5 parts of zirconium-copper alloy powder, 3-6 parts of silicon dioxide powder, 35-50 parts of epoxy resin, and 0.5-1.5 parts of external curing agent.
[0006] A method for preparing a filled high thermal conductivity composite press-in material comprises the following steps:
[0007] Step 1: Mixing powders: First, mix copper powder and zirconium-copper alloy powder (Zr-Cu) in proportion to ensure that Zr is fully dispersed in the Cu matrix, then add the mixed powder and silicon carbide, diamond, and boron nitride into a ball mill and mix for 12 h; finally, add silicon dioxide powder and carbon nanotubes and mix them in a mixer for 1 h;
[0008] Step 2: Add the mixture obtained in step 1 into the epoxy resin solution and stir for 30 minutes, and add a curing agent to obtain a filled high thermal conductivity composite press-fit material.
[0009] Wherein, silicon carbide is fine powder with particle size less than 0.065 mm.
[0010] Among them, the particle size of boron nitride is 0.5-5µm.
[0011] Among them, diamond is at the nanoscale.
[0012] Wherein, the curing agent is hexamethylenetetramine.
[0013] Epoxy resin has gradually replaced metal as the most widely used thermal conductive medium material due to its chemical corrosion resistance, low shrinkage, strong chemical inertness, strong plasticity, and excellent electrical insulation properties. The thermal conductivity of filled epoxy resin-based composite materials is mainly completed by the thermal conductivity of the filler. After the introduction of thermal conductive fillers, many interfaces are formed between fillers and fillers, and between fillers and epoxy resin matrix. In addition, the polarity of epoxy resin matrix and thermal conductive fillers is different, and the interface compatibility is very poor. Fillers are difficult to effectively disperse in epoxy resin, and the surface of fillers is difficult to be effectively wetted by epoxy resin base. There is a certain interface thermal resistance between epoxy resin and fillers, and the heat transfer efficiency per unit mass of filling materials is low. These factors lead to low efficiency in improving the thermal conductivity of composite materials.
[0014] The above-mentioned problem is solved by introducing a multi-component hybrid system to fill the polymer matrix and using an in-situ composite method to prepare a thermally conductive composite material. In the multi-component hybrid filling system, epoxy resin is used as a thermally conductive medium material, nano-diamond particles are wrapped on the surface of carbon nanotubes to form a binary composite filler as a reinforcing phase, and copper is used as a metal matrix. The copper particles are connected to adjacent boron nitride particles and applied to the surface of a continuous carbon fiber tape, and Zr elements are introduced into the copper matrix as a carbide-forming element to optimize the Cu-C interface. By selecting fillers with high thermal conductivity and improving the heat exchange efficiency per unit mass, the filler particles are in contact with each other, the interface thermal resistance is reduced, and a continuous chain or mesh structure of a 3D thermal conductive network path is formed in the polymer matrix. The advantages of the metal and the reinforcing phase are combined, and the good thermal conductivity and mechanical properties of copper and the high thermal conductivity, low density, and low thermal expansion coefficient of carbon nanotubes and diamonds are combined to improve the thermal conductivity of the epoxy resin-based composite press-fit material and improve its mechanical properties and thermal stability.
[0015] Nanodiamond particles are wrapped on the surface of carbon nanotubes to form a binary composite filler which is then evenly dispersed in epoxy resin, which effectively improves the dispersibility of the filler in the polymer matrix and forms a 3D thermal conduction path in the epoxy resin, enabling the construction of a continuous thermal conduction path for the composite material, greatly improving the thermal conductivity of the composite material. This method is simple and easy to operate, has no chemical pollution, and can also achieve high thermal conductivity of the composite material at a low filler content.
[0016] Boron nitride itself has the characteristics of low dielectric constant, low dielectric loss, high resistivity, large thermal expansion coefficient, good thermal stability, etc., and the thermal conductivity gradient of boron nitride is in the middle gradient of the thermal conductivity values of various fillers, making it an excellent choice for filled epoxy resin-based thermal conductive composite materials. Epoxy resin is selected as the matrix for preparing thermal conductive composite materials, and compounded with boron nitride filler. The composite material has high thermal conductivity and excellent mechanical properties. Boron nitride is mixed into thermosetting epoxy resin, and the boron nitride is dispersed at the structural interface to form a 3D thermal conductive network. The thermal conductivity of the composite material is significantly improved. The filler boron nitride is introduced into the system in the form of 3D, which effectively inhibits the movement of molecular segments in epoxy resin. Boron nitride particles can absorb part of the heat while delaying the decomposition of epoxy resin, improving the thermal stability of the composite material and having better dispersion stability.
[0017] The filled high thermal conductivity composite press-in material prepared by the present invention optimizes the formula combination according to the demand for product materials in actual field applications, constructs a multi-component mixed filling system with epoxy resin as the thermal conductive medium material, and by selecting fillers with high thermal conductivity and improving the heat exchange efficiency per unit mass, the filler particles are in contact with each other, the interface thermal resistance is reduced, and a 3D thermal conductive network path with a continuous chain or mesh structure is formed in the polymer matrix. The respective advantages of the metal and the reinforcement phase are combined to improve the thermal conductivity of the epoxy resin-based composite material, improve its mechanical properties and thermal stability, improve the integrity of the furnace body, and increase the service life of the blast furnace; the in-situ composite method is adopted for preparation, the process is simple, the production efficiency is high, and it is suitable for industrial production. DETAILED DESCRIPTION
[0018] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. The following implementation examples are intended to illustrate the present invention rather than further limit the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0019] Embodiment 1:
[0020] A filled high thermal conductivity composite press-in material is made of the following raw materials in parts by weight: 35 parts of silicon carbide, 10 parts of nano-diamond powder, 3 parts of carbon nanotubes, 5 parts of boron nitride with a particle size of 0.5-2µm, 2 parts of copper powder, 2 parts of zirconium-copper alloy powder, 3 parts of silicon dioxide micropowder, 0.5 parts of hexamine, and 35 parts of epoxy resin.
[0021] A method for preparing a filled high thermal conductivity composite press-in material comprises the following steps:
[0022] Step 1: Mixing powders: First, mix copper powder and zirconium-copper alloy powder (Zr-Cu) in proportion to ensure that Zr is fully dispersed in the Cu matrix, then add the mixed powder and silicon carbide, diamond, and boron nitride into a ball mill and mix for 12 h; finally, add silicon dioxide powder and carbon nanotubes and mix them in a mixer for 1 h;
[0023] Step 2: Add the mixture obtained in step 1 into the epoxy resin solution and stir for 30 minutes, and add a curing agent to obtain a filled high thermal conductivity composite press-fit material.
[0024] Embodiment 2:
[0025] A filled high thermal conductivity composite press-in material is made of the following raw materials in parts by weight: 40 parts of silicon carbide, 12 parts of nano-diamond powder, 5 parts of carbon nanotubes, 8 parts of boron nitride with a particle size of 1-2µm, 3 parts of copper powder, 3 parts of zirconium-copper alloy powder, 5 parts of silicon dioxide micropowder, 1 part of hexamethylenetetramine, and 40 parts of epoxy resin.
[0026] A method for preparing a filled high thermal conductivity composite press-in material comprises the following steps:
[0027] Step 1: Mixing powders: First, mix copper powder and zirconium-copper alloy powder (Zr-Cu) in proportion to ensure that Zr is fully dispersed in the Cu matrix, then add the mixed powder and silicon carbide, diamond, and boron nitride into a ball mill and mix for 12 h; finally, add silicon dioxide powder and carbon nanotubes and mix them in a mixer for 1 h;
[0028] Step 2: Add the mixture obtained in step 1 into the epoxy resin solution and stir for 30 minutes, and add a curing agent to obtain a filled high thermal conductivity composite press-fit material.
[0029] Embodiment 3:
[0030] A filled high thermal conductivity composite press-in material is made of the following raw materials in parts by weight: 50 parts of silicon carbide, 10 parts of nano-diamond powder, 5 parts of carbon nanotubes, 6 parts of boron nitride with a particle size of 1-2µm, 5 parts of copper powder, 3 parts of zirconium-copper alloy powder, 4 parts of silicon dioxide micropowder, 1 part of urotropine, and 45 parts of epoxy resin.
[0031] A method for preparing a filled high thermal conductivity composite press-in material comprises the following steps:
[0032] Step 1: Mixing powders: First, mix copper powder and zirconium-copper alloy powder (Zr-Cu) in proportion to ensure that Zr is fully dispersed in the Cu matrix, then add the mixed powder and silicon carbide, diamond, and boron nitride into a ball mill and mix for 12 h; finally, add silicon dioxide powder and carbon nanotubes and mix them in a mixer for 1 h;
[0033] Step 2: Add the mixture obtained in step 1 into the epoxy resin solution and stir for 30 minutes, and add a curing agent to obtain a filled high thermal conductivity composite press-fit material.
[0034] Embodiment 4:
[0035] A filled high thermal conductivity composite press-in material is made of the following raw materials in parts by weight: 55 parts of silicon carbide, 15 parts of nano-diamond powder, 8 parts of carbon nanotubes, 8 parts of boron nitride with a particle size of 2-5µm, 6 parts of copper powder, 5 parts of zirconium-copper alloy powder, 6 parts of silicon dioxide micropowder, 1.5 parts of urotropine, and 50 parts of epoxy resin.
[0036] A method for preparing a filled high thermal conductivity composite press-in material comprises the following steps:
[0037] Step 1: Mixing powders: First, mix copper powder and zirconium-copper alloy powder (Zr-Cu) in proportion to ensure that Zr is fully dispersed in the Cu matrix, then add the mixed powder and silicon carbide, diamond, and boron nitride into a ball mill and mix for 12 h; finally, add silicon dioxide powder and carbon nanotubes and mix them in a mixer for 1 h;
[0038] Step 2: Add the mixture obtained in step 1 into the epoxy resin solution and stir for 30 minutes, and add a curing agent to obtain a filled high thermal conductivity composite press-fit material.
[0039] The test results of the filled high thermal conductivity composite press-in materials obtained in Examples 1-4 are shown in the following table:
[0040]
Claims
1. A filled high thermal conductivity composite press-in material, characterized in that: It is made of the following raw materials in parts by weight: 35-55 parts of silicon carbide, 10-15 parts of diamond, 3-10 parts of carbon nanotubes, 5-10 parts of boron nitride, 2-8 parts of copper powder, 2-5 parts of zirconium-copper alloy powder, 3-6 parts of silicon dioxide powder, 35-50 parts of epoxy resin, and 0.5-1.5 parts of an external curing agent, wherein the diamond is nanometer-grade; The preparation method of the filled high thermal conductivity composite press-in material comprises the following steps: Step 1, powder mixing: first, copper powder and zirconium copper alloy powder (Zr-Cu) are mixed in proportion to ensure that Zr is fully dispersed in the Cu matrix, and then the mixed powder is added together with silicon carbide, diamond, and boron nitride and mixed in a ball mill for 12 hours; finally, silicon dioxide powder and carbon nanotubes are added and mixed in a mixer for 1 hour; Step 2: Add the mixture obtained in step 1 into the epoxy resin solution and stir for 30 minutes, and add a curing agent to obtain a filled high thermal conductivity composite press-fit material.
2. The filled high thermal conductivity composite press-in material according to claim 1, characterized in that: Silicon carbide is a fine powder with particles less than 0.065 mm.
3. The filled high thermal conductivity composite press-in material according to claim 1, characterized in that: The particle size of Boron Nitride is 0.5-5µm.
4. The filled high thermal conductivity composite press-in material according to claim 1, characterized in that: The curing agent is hexamethylenetetramine.
Citation Information
Patent Citations
Diamond powder-copper powder high-heat-conductivity composite material for LED (Light Emitting Diode) and preparation method of diamond powder-copper powder high-heat-conductivity composite material
CN106633662A
Boron nitride composite high-thermal-conductivity insulating polymer composite material and preparation method thereof
CN110951254A